Reluctant policy innovation through profit concession and informality tolerance: A strategic relational view of policy entrepreneurship in China's urban redevelopment. (8th September 2019) - Hu, Fox Z.Y.; Lin, George C.S.; Yeh, Anthony G.O.; He, Shenjing; Liu, Xingjian
Summary: This paper engages with the theoretical perspective of policy entrepreneurship to examine the pattern and process of policy change in the context of China's urban redevelopment. Drawing upon a strategic‐relational reinterpretation of policy entrepreneurship, this paper identifies a distinctive form of reluctant policy innovation in the "three old renewals" scheme initiated in Guangzhou where profit concession and informality tolerance were practiced to create a small window of opportunity for the project of urban redevelopment to break ground. The motivation of policy entrepreneurship in the successful urban renewal projects in Guangzhou was heavily contingent upon the geographically important location of the project site and the historically incidence of hosting the 2010 Asian Games, which forced municipal government to become entrepreneurial and innovative in decision making and income redistribution in order to get things done as quickly as possible. The distinct fashion of policy innovation identified in the case of Guangzhou points to the polymorphous and dynamic nature of policy entrepreneurship and advocates a relational treatment of the strategies and motives of policy entrepreneurs embedded in concrete geographical and historical context.